The effect of vitamin E on the quality of geese meat - Danchenko, Mykola; Данченко, Микола Миколайович; Данченко, Николай Николаевич; Ruban, H.; Danchenko, Olena; Данченко, Олена Олександрівна; Данченко, Елена Александровна; Yakoviichuk, O.; Klimashevskyi, V.; Konovalenko, T.; Sukharenko, Olena; Сухаренко, Олена Іванівна; et al. (Lietuvos mokslų akademija, 2019)
EN: During prolonged storage at low temperatures, meat quality deteriorates due to the activation of the oxidation of unsaturated fatty acids. The use of antioxidants in feeding birds to the prefabricated period and during storage of meat significantly inhibits its oxidative damage and prolongs the terms of storage. Vitamin E is traditionally used as one of the most effective fat-soluble antioxidants. The purpose of the work was conducting a comparative analysis of the effects of high content of vitamin E, depending on the technology of its application, on the oxidative damage of geese meat in the course of low temperature storage. The meat of the first experimental sample was obtained from geese that received feed with twice the content of vitamin E in the pre-slaughter period. The meat of the second test sample was obtained by treating geese meat with a vitamin E solution, before low temperature storage. The results of the experiment proved that regardless of the technology of vitamin E application, it contributes to the inhibition of the oxidative damage. An increase of vitamin E dose in the geese dietary is more effective . The content of secondary lipoperoxidation products in the meat of the control sample stored for 210 days increased by 5.3 times, in the first test sample by 2.5 times, and in the second sample by 4.6 times. An additional use of vitamin E in both studied samples contributed to the preservation of unsaturated fatty acids, but the mechanisms of exposure and changes in the content of individual acids in experimental samples are significantly different. LT: Ilgai laikant mėsą žemoje temperatūroje, jos kokybė blogėja dėl nesočiųjų riebalų rūgščių oksidacijos. Antioksidantų naudojimas paukščių pašaruose slopina oksidacinę žalą paukštienai ir prailgina mėsos laikymo laikotarpį. Vitaminas E tradiciškai naudojamas kaip vienas efektyviausių riebaluose tirpių antioksidantų. Darbo tikslas – didelės koncentracijos vitamino E poveikio palyginamoji analizė, atsižvelgiant į jo taikymo technologijas žąsienos oksidacinei žalai slopinti, kai mėsa laikoma žemoje temperatūroje. Pirmojo bandinio mėsa buvo žąsies, kuri prieš skerdimą buvo šeriama dviguba vitamino E doze. Antrojo mėginio mėsa iki saugojimo žemoje temperatūroje buvo laikyta vitamino E tirpale. Eksperimento rezultatai patvirtino, kad kokia bebūtų vitamino E panaudojimo technologija, jis prisideda prie oksidacinio pažeidimo slopinimo. Veiksmingesnis yra vitamino E dozės didinimas paukščių pašaruose. Antrinių lipoperoksidacijos produktų kiekis kontrolinėje mėsoje po 210 dienų laikymo padidėjo 5,3 karto, pirmojo mėginio – 2,5 karto, o antrojo – 4,6 karto. Papildomas vitamino E naudojimas abiejuose tirtuose mėginiuose prisidėjo prie nesočiųjų riebalų rūgščių išsaugojimo, tačiau ekspozicijos mechanizmai ir individualūs rūgščių kiekio pokyčiai eksperimentiniuose mėginiuose labai skiriasi.
Keywords: geese; meat; storage; oxidation damage; α-tocopherol; žąsiena; mėsa; laikymas; oksidacinė žala; α-tokoferolis